Financial inclusion for persons with disabilities: Experiences of providers and users of financial products and services in Kenya. - Sheru W. Muuo; Bhavisha Virendrakumar; George Okello; Moses Chege; Vibian Angwenyi; Kenneth Gichohi; Hillary Kibet; Sally Nduta; Stevens Bechange; Elena Schmidt; Simon Brown; Emma Jolley (PLoS ONE, 2025)
Background Inclusion of persons with disabilities in financial products and services has been identified as an important step on the pathway to achieving the sustainable development goals. Evidence of how people with disabilities are included in financial products and services including strategies to improve their inclusion in low and middle-income countries is limited. We draw on qualitative data to to understand the experiences of providing and using financial products and services from the perspectives of persons with disabilities and representatives of different financial institutions in Nairobi and Migori counties of Kenya. Methods Eighty-one persons with disabilities (49.4% <35 years, 57% female) were purposively sampled to take part in 10 focus group discussions. Additionally, 26 in-depth interviews were conducted with financial institution representatives. Data were collected between July and September 2022 and analysed thematically. Results Participants described a mixed picture, sharing experiences of different levels of inclusion, and examples of exclusion from different types of financial services and products. Despite good intentions, financial institutions lacked the knowledge and skills required to adapt existing financial products and services, and marketing strategies for different needs and to improve the accessibility of products and services for persons with disabilities. The findings highlighted a need for staff training and establishing institutional policies and guidelines to support the inclusion of persons with disabilities. Persons with disabilities reported embracing digital financial services and constitute a large untapped market for the financial institutions who are able to provide accessible products and services. Conclusion Multi-stakeholder approaches are needed to increase disability awareness, develop and enforce policies and guidelines as well as collection of disability-disaggregated data to promote financial inclusion for persons with disabilities in Kenya.